1969
DOI: 10.1530/acta.0.061s053
|View full text |Cite
|
Sign up to set email alerts
|

Equilibration of Plasma and Adrenal Cholesterol in Man

Abstract: J Appl Physiol 28:42-49 (Jan) 1970 The equilibration of plasma and adrenal cholesterol was investigated during seven days after 14C-cholesterol admin¬ istration in 24 patients undergoing bilateral adrenalectomy for generalized mammary carcinoma. The specific activi¬ ties (SA) of free adrenal cholesterol increased very rapid¬ ly and tended toward those of free plasma cholesterol. They were higher than those for esterified plasma cho¬ lesterol during the first two days and followed the curve of total plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…From a qualitative point of view and with the exception of the most unsaturated cholesteryl esters (A4) the pattern of the in vitro esterification is comparable to that previously found in vivo (4). Indeed, the specific activities of cholesterol in the various esters are fairly similar to each other, indicating that the distribution of the newly formed cholesteryl esters is similar to that already present before incubation; this is particularly striking for the A1 and A2 cholesteryl esters (essentially oleate and linoleate) which are the most abundant and are found in reversed proportions in plasma (26) and in the adrenal cortex (19).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…From a qualitative point of view and with the exception of the most unsaturated cholesteryl esters (A4) the pattern of the in vitro esterification is comparable to that previously found in vivo (4). Indeed, the specific activities of cholesterol in the various esters are fairly similar to each other, indicating that the distribution of the newly formed cholesteryl esters is similar to that already present before incubation; this is particularly striking for the A1 and A2 cholesteryl esters (essentially oleate and linoleate) which are the most abundant and are found in reversed proportions in plasma (26) and in the adrenal cortex (19).…”
Section: Discussionsupporting
confidence: 82%
“…In vitro synthesis of adrenal cholesterol from acetate-2-'4C. The adrenal glands obtained in the operating room were immediately placed in a solution of Krebs-Ringer-bicarbonate and processed in the cold room as previously described (3,4). The slices of adrenal tissue were then incubated, during 3 hr, at 370C, in a metabolic incubator, under constant agitation and in an atmosphere of 95% oxygen and 5%o carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in humans (19,20) and rats (21,22) have demonstrated that 80% or more of the cholesterol as a substrate for adrenal steroidogenesis might come from plasma, especially from plasma lipoproteins (23)(24)(25). These reports suggested that cholesterol esters which were used for steroidogenesis were stored as lipid droplets, and that free cholesterol for steroidogenesis was mainly provided by hydrolysis of the deposited cholesterol ester by CEase (3,9,26).…”
Section: Discussionmentioning
confidence: 99%
“…This represents a new theoretical treatment of data previously obtained in 24 patients undergoing bilateral adrenalectomy for generalized mammary carcinoma (2). Cholesterol4-14C was administered i.v.…”
Section: Methodsmentioning
confidence: 99%
“…The role of free adrenal cholesterol in the structure of the membranes makes it imperative for reasons of structural stability that its concentration be constant. It is indeed remarkable how free adrenal cholesterol varies little despite important variations of the adrenal functional state (2).…”
Section: Parameters Of Adrenal Cholesterol In Control Studiesmentioning
confidence: 99%